2005
DOI: 10.1111/j.1365-3091.2005.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, lateral variability and lateral extent of discontinuity surfaces on a Carbonate Platform (Barremian to Lower Aptian, Oman)

Abstract: Hiati of various duration in carbonates are commonly expressed as discontinuity surfaces. The understanding of processes that form and affect these surfaces leads to an improved sequence-stratigraphic interpretation, a reliable outcrop correlation, and better models for reservoir compartmentalization. Various intraformational discontinuities were analysed and interpreted in a wellexposed study window, 2AE5 km in lateral length and 60 m in height comprising the Barremian-Aptian Qishn Formation (Haushi-Huqf area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(119 citation statements)
references
References 50 publications
5
111
1
2
Order By: Relevance
“…The low δ 13 C values could be related to the influence 13 C-depleted soil-zone CO2 that affected the bulk isotopic composition of supratidal facies (Allan & Matthews 1977;Allan & Matthews 1982;Immenhauser et al 2003). Indeed, negative carbon isotope trends are commonly believed to result from the uptake of light carbon derived from the deterioration of organic material in soils during subaerial exposure (Allan & Matthews 1982;Lohman 1988;Sattler et al 2005). The depleted composition of δ 18 O could be explained by the influence of 18 O-depleted early meteoric fluids linked to meteoric diagenesis of marine carbonates above the water table.…”
Section: Discussion: Origin Of the Isotopic Signalmentioning
confidence: 99%
“…The low δ 13 C values could be related to the influence 13 C-depleted soil-zone CO2 that affected the bulk isotopic composition of supratidal facies (Allan & Matthews 1977;Allan & Matthews 1982;Immenhauser et al 2003). Indeed, negative carbon isotope trends are commonly believed to result from the uptake of light carbon derived from the deterioration of organic material in soils during subaerial exposure (Allan & Matthews 1982;Lohman 1988;Sattler et al 2005). The depleted composition of δ 18 O could be explained by the influence of 18 O-depleted early meteoric fluids linked to meteoric diagenesis of marine carbonates above the water table.…”
Section: Discussion: Origin Of the Isotopic Signalmentioning
confidence: 99%
“…In addition, Gastrochaenolites and Trypanites have been reported repeatedly from discontinuity surfaces and hardgrounds (e.g. Bromley 1975;Kobluk et al 1977;Helm 1998;Wilson and Taylor 2001;Mikulas et al 2003;Benner et al 2004;Sattler et al 2005). Within ancient rocky shore complexes of transgressive sequences, Gastrochaenolites is often found in mobile pebble substrates that can be reworked within shallow-water transgressive sequences (e.g.…”
Section: Gastrochaenolites Boringsmentioning
confidence: 95%
“…It is therefore the combination of autogenic/autocyclic and allogenic/allocyclic processes that is responsible for sediment deposition and the formation of the final sedimentary record. Many case studies have already shown and discussed the coexistence of autocyclic and allocyclic processes, for example: Sami and James (1994) in the Proterozoic of northwest Canada; Jiang et al (2003) in the Proterozoic of the Lesser Himalaya; Adams and Grotzinger (1996) in the Middle Cambrian of California; Cowan and James (1993) in the Late Cambrian of Newfoundland; Smith and Read (2001) in the Mississippian of Illinois; Yang et al (1998) in the Late Pennsylvanian and Early Permian of Texas; Bádenas et al (2010) in the Sinemurian of Spain; Carpentier et al (2010) in the Oxfordian of France; Sattler et al (2005) in the Barremian and Aptian of Oman; Lehmann et al (1998) in the Barremian to Albian of northeastern Mexico; Rankey (2002) in the Holocene of the Bahamas.…”
Section: Autocyclic Processesmentioning
confidence: 99%